Idiopathic gingival fibromatosis in association with aggressive periodontitis and candidal infection: A unique case report with 7-year follow-up - Anuradha Bhatsange; Anuja Moharir; Vibhuti Mistry; Sharanbasappa Japatti (Wolters Kluwer Medknow Publications, 2021)
Idiopathic gingival fibromatosis, also called idiopathic gingival overgrowth (IGO), is a rare benign condition that occurs either in isolation or as a part of a syndrome. The overgrowth, if excess, impedes oral functions such as mastication and speech and causes cosmetic disfigurement. Diagnosis and treatment becomes challenging if the overgrowth is massive and accompanies other associated pathologies. This case reports concurrent occurrence of three pathologies, i.e., IGO, aggressive periodontitis, and candidal infection in a 20-year-old healthy male patient. The surgical procedure performed involved internal bevel gingivectomy combined with open-flap surgery. Seven-year follow-up revealed no recurrence of overgrowth and stable periodontal condition.